Diagnostic challenges in imaging and immunohistopathological profiles in extraskeletal osteosarcoma - Jiro Ichikawa; Tomonori Kawasaki; Kojiro Onohara; Kaoru Aoki; Masanori Wako; Satoshi Ochiai; Tetsuo Hagino; Hirotaka Haro (World Journal of Surgical Oncology)
Abstract This correspondence addresses the article published by Nie et al. titled “Primary extraskeletal osteosarcoma of sigmoid mesocolon: a case report and a review of the literature”. Their report highlighted an extremely rare case of extraskeletal osteosarcoma (EO) in the sigmoid mesocolon that was diagnosed through imaging and histopathological findings. Diagnosing EO has certain challenges; one of them being the lack of characteristic image findings of EO and the other being the lack of appropriate immunohistochemical (IHC) markers in the histopathological findings. Recently, special AT-rich sequence-binding protein 2 (SATB2) has been proposed as an IHC marker for osteoblastic differentiation; however, it has low specificity. Some cases of EO may show findings such as mouse double minute protein 2 expression and deletion of histone H3 lysine 27 trimethylation (H3K27me3), which are similar to those of other soft tissue sarcomas. Therefore, it is essential to consider other soft tissue sarcomas, especially dedifferentiated liposarcoma, before the accurate diagnosis of EO.